CNT Interwoven Nitrogen and Oxygen Dual‐Doped Porous Carbon Nanosheets as Free‐Standing Electrodes for High‐Performance Na‐Se and K‐Se Flexible Batteries. Issue 49 (9th October 2018) - Yao, Yu; Chen, Minglong; Xu, Rui; Zeng, Sifan; Yang, Hai; Ye, Shufen; Liu, Fanfan; Wu, Xiaojun; Yu, Yan
Abstract: Na‐Se and K‐Se batteries are attractive as a stationary energy storage system because of much abundant resources of Na and K in the Earth's crust. As the alloy‐type Se has a severe pulverization issue, one critical challenge to develop advanced Na‐Se and K‐Se batteries is to explore a highly efficient and stable Se‐based cathode. Herein, a flexible free‐standing Se/carbon composite film is prepared by encapsulation of Se into a carbon nanotube (CNT) interwoven N, O dual‐doped porous carbon nanosheet (Se@NOPC‐CNT). The 3D interconnected CNT uniformly wrapped on the N, O dual‐doped porous carbon skeletons improves the flexibility and offers an interconnected conductive pathway for rapid ionic/electronic transport. In addition, the N, O dual‐doping significantly enhances the chemical affinity and adhesion between Na x Se/K x Se (0 < x ≤ 2) and porous carbon, which is confirmed by density functional theory calculation. When used as the cathode in Na‐Se batteries, the Se@NOPC‐CNT delivers a remarkable reversible capacity of 400 mA h g −1 at 1 A g −1 after 2000 cycles with a 0.008% capacity decay per cycle. For K‐Se batteries, it also exhibits an excellent cycling stability (335 mA h g −1 after 700 cycles at 0.8 A g −1 ). This unique design may open an avenue for practical application of flexible Na‐Se and K‐Se batteries. Abstract : Se is encapsulated in a carbon nanotube (CNT) interwoven N, O dual‐doped porous carbon nanosheet (Se@NOPC‐CNT), which can be used as a flexible free‐standing cathode for both Na‐Se and K‐Se batteries. The Se@NOPC‐CNT electrodes display excellent sodium/potassium storage properties, including high reversible capacity, good rate capability, and ultralong cycling lifetime.